Melon Thrips, Thrips palmi Karny (Thysanoptera: Thripidae) - John L. Capinera (EDIS, 2002)
This document is EENY-135, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2000.